To the knowledge of the spider fauna (Aranei) of the Republic of Mordovia (Russia) - S.L. Esyunin (Russian Academy of Science. Southern Scientific Centre. Federal Research Centre, 2020)
Here we present faunistic, partly ecological and biogeographic data on Aranei, collected in 11 districts of the Republic of Mordovia (Russia), typical area of the center of the East European Plain. The araneofauna of this region is poorly studied and our new data help to correct biogeorgaphic limits of many species. Spiders were collected by soil traps in April–July 2008 and 2012. In total, 131 species from 18 families are listed, 57 of them are recorded for the Republic of Mordovia for the first time (marked by asterisks in the check-list). The following records are the most interesting for biogeography and bionomics in different parts of ranges: Agyneta fuscipalpa (C.L. Koch, 1836) (rare, but widespread species, which is known from semiarid and semihumid areas of the Palaearctic); Alopecosa taeniopus (Kulczyński, 1895) (the range of this species is limited by steppe zone of the Palaearctic from the Balkans to West China; it inhabits many biotopes from salt marshes to outlier and ravine forests in the forest-steppe and in the steppe zones of the East European Plain); Cheiracanthium campestre Lohmander, 1944 (a rare European species, which was registered within the East European Plain only in Rostov Region), Pardosa alacris (C.L. Koch, 1833) (widespread in Europe, confined to the subboreal zone of the East European Plain), Pardosa maisa Hippa et Mannila, 1982 (habitats of the Mordovian populations of this species are unusual; it occurs in Europe in waterlogged habitats: swamps, floodplain wet meadows, salt marshes, reed shores of lakes, very rarely and sporadically in moderately dry meadows or grasslands; this species is also confined to the shores of lakes in Western Siberia; specimens collected in Mordovia and in the Privolzhsky Forest-Steppe Reserve in Penza Region were found in dry grassy habitats), Peponocranium praeceps Miller, 1943 (a rare European species, occurring in forests, meadows and swamps in Europe, but exclusively in xerophytic meadows in teppes of the Cis-Ural region), Trichoncus hackmani Millidge, 1955. In total 228 species of spiders are known now in Mordovia. The basis of the araneofauna of Mordovia consists of spiders typical for the subboreal zone of the European part of Russia.